Mixed Ionic and Electronic Conduction in Radical Polymers - Yu, Ilhwan; Jeon, Daeyoung; Boudouris, Bryan; Joo, Yongho (AMER CHEMICAL SOC, 2020)
Organic mixed ionic and electronic conductors typically have heterogeneous conjugated macromolecular backbones and ether-based pendant groups to transport ions and charges. Moving from this archetype toward one with a single component, nonconjugated redox-active radical polymers that conduct both the charge and mass have significant benefits, such as they can be readily synthesized in large quantities and have the ability to produce either hole- or electron-transporting radical polymers by the selective tuning of the pedant group chemistry. Here, we demonstrate long-range (i.e., for lengths >50 mu m) operational mixed ionic and electronic conduction in an amorphous, nonconjugated, low-glass-transition-temperature organic radical polymer upon blending the macromolecule with an ionic dopant lithium bis(trifluoromethanesulfonyl)imide salt (LiTFSI). Tuning the precise chemical nature of the functional radical pedant group using this ionic dopant is of key importance for the enhancement of long-range electrical conductivity. Moreover, the maximum ionic conductivity was 10(-3) S cm(-1) at elevated temperatures, and this was the highest reported value for a radical polymer-based system. Our findings demonstrate a significantly different macromolecular design paradigm than the commonly accepted heterogeneous composition for the creation of next-generation organic mixed ionic and electronic conductors.
Keywords: LIGHT-EMITTING-DIODES; NITROXIDE RADICALS; CHARGE-TRANSPORT; ELECTROLYTES; BATTERIES; EMISSION; DYNAMICS; FUTURE; STATE